Integration of Sustainable Development into International Marketing: Developing a Mechanism for Enhancing Enterprise Economic Potential in Wartime Conditions - Tanasiichuk, Alona; Dybchuk, Liudmyla; Prysiazhna, Lyudmila; Sokolyuk, Katerina; Vyshniuk, Vitalii; Kashpruk, Yulia; Serednytska, Liudmila (European Journal of Sustainable Development, 2025)
<!--StartFragment --> <!--StartFragment --> Secondary processes in hospitals, such as procurement and outsourced services, significantly contribute to their carbon footprint. However, driving sustainability in these areas is challenging due to limited hospital control and the involvement of external actors. This study investigates factors influencing sustainable change in secondary hospital processes in Germany, using a framework that categorizes change drivers at micro-, meso-, and macro-levels. Through qualitative interviews with eleven experts from hospitals and service providers, the research highlights the importance of inter-organisational collaboration and structural redesign to enable coordinated sustainability efforts. Findings reveal that current hospital-service provider relationships are primarily cost-driven, limiting transformational potential. Yet, sustainability offers a pathway to redefine roles and build resilient partnerships. In parallel, the study examines how Ukrainian enterprises are integrating sustainability into international marketing under wartime conditions. It analyzes export trends from 2020 to 2024, focusing on the mining sector, particularly “26 Ores, Slag and Ash.” The research identifies promising markets (Netherlands, South Korea, Japan, and the U.S.) and recommends tailored entry strategies considering political stability, trade openness, and logistics. Strategic partnerships, infrastructure development, and participation in global trade forums are emphasized as key to resilience.Together, these findings underscore the need for multi-actor cooperation and sustainability integration in both healthcare and international business. The study offers practical guidance for hospitals and Ukrainian enterprises to align operational processes with long-term ecological and economic goals, even amid geopolitical disruption. Keywords: sustainable development integration, international marketing, economic potential of enterprises, sustainability strategies, export activity dynamics, geopolitical changes, economic recovery, enterprise competitiveness, wartime risks, logistics infrastructure, economic dynamics, trade freedom, logistics capacity, economic security <!--EndFragment -->